2017
DOI: 10.5020/18061230.2017.p170
|View full text |Cite
|
Sign up to set email alerts
|

Perfil de idosos submetidos à avaliação geriátrica ampla em serviço de reabilitação

Abstract: Este artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons, que permite uso, distribuição e reprodução em qualquer meio, sem restrições, desde que o trabalho seja corretamente citado. PERFIL DE IDOSOS SUBMETIDOS À AVALIAÇÃO GERIÁTRICA AMPLA EM SERVIÇO DE REABILITAÇÃOProfi le of older people submitted to comprehensive geriatric assessment in a rehabilitation service Perfi l de ancianos sometidos a una amplia evaluación geriátrica de un servicio de rehabilitación Fernanda Silva RochaPont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In this study, the sociodemographic characteristics of the elderly are similar to those found in other studies with Brazilian elderly receiving outpatient care. The mean for age was of 77.7 years ( 25 ) , there was predominance of females ( 26 ) , low schooling ( 27 ) , and widowhood ( 28 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the sociodemographic characteristics of the elderly are similar to those found in other studies with Brazilian elderly receiving outpatient care. The mean for age was of 77.7 years ( 25 ) , there was predominance of females ( 26 ) , low schooling ( 27 ) , and widowhood ( 28 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of low schooling among the elderly reflects the national reality. The higher the age, the lower the schooling level ( 27 ) . Specifically, among the elderly, low education predisposes to unfavorable economic conditions, since they were in the informal market throughout their lives, with no planning and investment possibilities to guarantee retirement ( 35 ) .…”
Section: Discussionmentioning
confidence: 99%
“…It is added that, for health services, the conditions in which people aged have a direct impact on the search for access. [3][4][5] The main negative impact of population aging is the increase in the prevalence of chronicdegenerative diseases, which are the main causes of mortality and disability worldwide, which increases the risk for hospitalization. [6][7] It is warned that another problem that has grown in the elderly population is external causes, characterized by accidents and violence and that should be the object of concern among health professionals.…”
mentioning
confidence: 99%
“…Porciúncula et al ( 50 ) reported that older adult men are more exposed to acute lethal diseases, such as heart ischemia. The predominance of the female population among the individuals aged 80 and over has important repercussions on the demands for public policies, since various studies show that despite living longer, women are susceptible to developing functional disabilities and multiple health problems and live with them for longer ( 37 , 70 ).…”
Section: Discussionmentioning
confidence: 99%